Role of Common Herbs- Curcuma Longa and Emblica Officinalis in Metabolic Disorders: A Narrative Review: Life Sciences-Ayurveda - Aman Chhabra, Dr.; Kuchewar, Dr. Vaishali; Twinkle Joshi, Dr. (International Journal of Life Science and Pharma Research, 2023)
In the present era, Metabolic disorder is a challenge to the medical community because of its increasing prevalence and unsatisfactory management. There is no permanent remedy, and the patient has to continue the medicine for a longer life. According to Ayurveda, all metabolic diseases are caused due to Jathragnimandya(improper digestion & metabolism). Hence the correction of Agni is the principle to treat it. Various herbs act as agnivardhak (increase digestive fire or Rasayan (Rejuvenator). Haridra (Curcuma longa) and Amalaki (Emblica Officinalis) are the herbal drugs recommended in Ayurveda literature. Ayurveda practitioners are using these medicines for various metabolic disorders. Hence this review was carried out to discover their utility in metabolic disorders. The aim and objective of this review are to study the role of common herbs available worldwide, which are Haridra (Curcuma longa) and Amalaki (Emblicaofficinalis), in metabolic disorders. The related data were collected from classical texts of Ayurveda, google scholar, and PubMed. A total of 10 articles were considered for review. Out of these, four were animal studies, and six were analytical studies in which the assessment parameters were fasting. From this review, few studies have been conducted on only Haridra as compared to Amalaki on the post-meal blood sugar levels, glycolatedhaemoglobin (HbA1c) levels, oral glucose tolerance test, and complete blood count metabolic disorders. The maximum studies are on Nisha-Amalaki(a combination of Haridra&Amalakialongwith bhavna[trituration process] of Amalakiswarasa[Juice form of Emblicaofficinalis]to Haridra[Curcuma longa]) which is found to be effective in Diabetes mellitus and dyslipidemia, which can be considered as the cavity of previous reviews. Therefore, there is a need to conduct studies on Nisha-amalaki to explore its effect on other common metabolic disorders like PCOD, Hypothyroidism.